2007
DOI: 10.1590/s0036-46652007000400007
|View full text |Cite
|
Sign up to set email alerts
|

T CD4+ cells count among patients co-infected with human immunodeficiency virus type 1 (HIV-1) and human T-cell leukemia virus type 1 (HTLV-1): high prevalence of tropical spastic paraparesis/HTLV-1-associated myelopathy (TSP/HAM)

Abstract: SUMMARYIntroduction: HIV positive patients co-infected with HTLV-1 may have an increase in their T CD4 + cell counts, thus rendering this parameter useless as an AIDS-defining event. Objective: To study the effects induced by the co-infection of HIV-1 and HTLV-1 upon CD4 + cells. Material and Methods: Since 1997, our group has been following a cohort of HTLV-1-infected patients, in order to study the interaction of HTLV-1 with HIV and/or with hepatitis C virus (HCV), as well as HTLV-1-only infected asymptomati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…Importantly, the incidence of HAM/TSP in coinfected patients with AIDS was 20 times higher than those infected with only HTLV-1 infection. These results supported previous observations that HTLV-1/HIV-1 coinfection was associated with a higher probability of a more severe HTLV-1 infection along with an increase in the levels of CD4 + T cells [3]. These results have suggested the possibility that HTLV-1 may inhibit HIV-1 replication with a subsequent increase in CD4 + T-cell counts, thereby enhancing HTLV-1 disease progression.…”
Section: Incidence Of Ham/tsp Among Htlv-1/hiv-1-coinfected Patientssupporting
confidence: 91%
See 2 more Smart Citations
“…Importantly, the incidence of HAM/TSP in coinfected patients with AIDS was 20 times higher than those infected with only HTLV-1 infection. These results supported previous observations that HTLV-1/HIV-1 coinfection was associated with a higher probability of a more severe HTLV-1 infection along with an increase in the levels of CD4 + T cells [3]. These results have suggested the possibility that HTLV-1 may inhibit HIV-1 replication with a subsequent increase in CD4 + T-cell counts, thereby enhancing HTLV-1 disease progression.…”
Section: Incidence Of Ham/tsp Among Htlv-1/hiv-1-coinfected Patientssupporting
confidence: 91%
“…One hundred and fifty HTLV-1-infected patients were enrolled in the study; 27 of them were coinfected with HIV-1, and 15 of the coinfected patients had already reported an AIDS-defining event. CD4 + T-cell counts were higher in coinfected individuals with AIDS than in HIV-1-monoinfected patients (median = 189 cells/mm 3 and 89 cells/mm 3 , respectively; p = 0.036). Moreover, five of the coinfected subjects who had AIDS and three of the coinfected patients without AIDS showed signs of HAM/TSP.…”
Section: Incidence Of Ham/tsp Among Htlv-1/hiv-1-coinfected Patientsmentioning
confidence: 89%
See 1 more Smart Citation
“…It should be noted that although preserved, these CD4 cells are functionally impaired and ART should be considered regardless of the CD4 counts in these patients. 22,23 HIV leads to increased HTLV protein expression. 24,25 These effects may be a possible explanation as to how HTLV is more readily able to overcome the immune response.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in some geographic regions 5-10% of HIV-1-infected individuals may be coinfected with HTLV-1 or HTLV-2. 3,4 Several recent studies suggest three conclusions regarding HIV/HTLV coinfections: (1) HIV-1 and HTLV-1 coinfections are often seen in the context of patients with high CD4 + T cell counts and who manifest neurological complications 5,6 ; (2) HIV-1 and HTLV-2 coinfections have been linked in some cases to a ''long-term nonprogressor'' phenotype 3,7 ; and (3) differential function and/or overexpression of the HTLV-1 and HTLV-2 Tax proteins are likely to play a pivotal role in the clinical and immunological manifestations of HIV/HTLV coinfections. 8 Two retrospective case-controlled cohort studies investigating the clinical outcomes and survival probabilities among persons coinfected with HIV-1 and HTLV-1 or -2 showed that HTLV-2 coinfections resulted in improved survival and delayed progression to AIDS.…”
Section: Introductionmentioning
confidence: 99%